The Association of Oxygenation, Carbon Dioxide Removal, and Mechanical Ventilation Practices on Survival During Venoarterial Extracorporeal Membrane Oxygenation - Justus, Angelo; Burrell, Aidan; Anstey, Chris; Cornmell, George; Brodie, Daniel; Shekar, Kiran (Frontiers in Medicine, 2021)
Introduction: Oxygenation and carbon dioxide removal during venoarterial extracorporeal membrane oxygenation (VA ECMO) depend on a complex interplay of ECMO blood and gas flows, native lung and cardiac function as well as the mechanical ventilation strategy applied. Objective: To determine the association of oxygenation, carbon dioxide removal, and mechanical ventilation practices with in-hospital mortality in patients who received VA ECMO. Methods: Single center, retrospective cohort study. All consecutive patients who received VA ECMO in a tertiary ECMO referral center over a 5-year period were included. Data on demographics, ECMO and ventilator support details, and blood gas parameters for the duration of ECMO were collected. A multivariable logistic time-series regression model with in-hospital mortality as the primary outcome variable was used to analyse the data with significant factors at the univariate level entered into the multivariable regression model. Results: Overall, 52 patients underwent VA ECMO: 26/52 (50%) survived to hospital discharge. The median PaO2 for the duration of ECMO support was 146 mmHg [IQR 131–188] and PaCO2 was 37.2 mmHg [IQR 35.3, 39.9]. Patients who survived to hospital discharge had a significantly lower median PaO2 (117 [98, 140] vs. 154 [105, 212] mmHg, P = 0.04) and higher median PaCO2 (38.3 [36.1, 41.1] vs. 36.3 [34.5, 37.8] mmHg, p = 0.03). Survivors also had significantly lower median VA ECMO blood flow rate (EBFR, 3.6 [3.3, 4.2] vs. 4.3 [3.8, 5.2] L/min, p = < 0.001) and greater measured minute ventilation (7.04 [5.63, 8.35] vs. 5.32 [4.43, 6.83] L/min, p = 0.01). EBFR, PaO2, PaCO2, and minute ventilation, however, were not independently associated with death in a multivariable analysis. Conclusion: This exploratory analysis in a small group of VA ECMO supported patients demonstrated that hyperoxemia was common during VA ECMO but was not independently associated with increased mortality. Survivors also received lower EBFR and had greater minute ventilation, but this was also not independently associated with survival. These findings highlight that interactions between EBFR, PaO2, and native lung ventilation may be more relevant than their individual association with survival. Further research is indicated to determine the optimal ECMO and ventilator settings on outcomes in VA ECMO.